If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-7+8(7x+6)=0
We simplify the equation to the form, which is simple to understand
-7+8(7x+6)=0
Reorder the terms in parentheses
-7+(+56x+48)=0
Remove unnecessary parentheses
-7+56x+48=0
We move all terms containing x to the left and all other terms to the right.
+56x=0+7-48
We simplify left and right side of the equation.
+56x=-41
We divide both sides of the equation by 56 to get x.
x=-0.73214285714286
| x+0.473684210526316+x=64-x-1 | | 2/3*(7a-14)/-28 | | x^4+-4x^3+2x^2=0 | | 2=500000/x | | 4-3=a | | 2s-5s=-15s+60 | | x-11+x-11+121+121=360 | | x+2y+3z=0 | | -4(x+8)=-32-4x | | 9y+3=5y+10 | | 11x+18=62 | | x+3+x-6=7-4 | | 2/3*7x-9/10 | | -3k-8+7=-21 | | 10y+6=5y+21 | | 1/3xd=1/10 | | x+9-19+x=64-x-1 | | 9=17+3x | | 100y+5=75y+25 | | 8(4-y)+10y=6y | | 19x+(-5)=-26+12x | | M=3m+10 | | 5x+10x+17x+4x=360 | | 16x^3-20x^2+12x-15= | | 4(2+2r)-2(-r+1)=6r+-2r | | M-8=3m+2 | | 21=6(5r-2) | | 3x+3-9=3+7-4 | | 2x+3(x-8)=9-5x | | 8x-25=6x-5 | | 100/15 | | -7x+23=-21-31x |